Silicon decorated graphene nanoplates modified anode and MnO2 interlayer as a multifunctional polysulfides barrier for advanced pre-lithiation silicon-sulfur batteries - Aslfattahi, Navid; Kiai, Maryam Sadat; Baydogan, Nilgun; Samylingam, Lingenthiran; Kadirgama, Kumaran; Kok, Chee Kuang
The development of advanced anodes with high capacity and excellent high-rate cycling performance for next generation of sulfur-based batteries has emerged as a significant area of research. In this study, we present a straightforward approach to design and fabricate silicon/graphene nanoplates using a one-step hydrothermal method. Notably, a pomegranate-like structure is achieved in the silicon/graphene nanoplates (Si/GNP) spheres, with distinctive porous pomegranate architecture not only enhances the electrical conductivity of the active silicon but also accommodates substantial volume changes during cycling. Additionally, to enhance redox reactions and hinder shuttle effect, GNP/MnO2 composites is investigated as an interlayer. The MnO2 particles are in-situ grown on the surface of the GNP. The metal oxide MnO2 can enhance chemical adsorption during the electrochemical cycles. As a result, the cell with GNP/MnO2interlayer and Si/GNP anode spheres exhibit remarkable cycling stability, delivering capacity retention of 986 mAh g− 1 after 300 cycles, indicating a commendable cycling performance. The cell performance was investigated across different current densities. Notably, substantial discharge capacities of 831 and 719 mAh g− 1 were attained even at 2C and 5C current densities. The synthetic approach we have developed presents an innovative route for high-performance practical anodes and interlayers intended for electrochemical energy storage applications.